Mengukur Brand Awarness Laptop Merek Zyrex Berdasarkan Persepsi Pengguna Laptop Di Yogyakarta - Dwi Wahyu Pril Ranto (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2010)
The brand awareness is a basic dimension in brand equity. One brand does not have any equity unless the consumers are awareness of the existence of the brand itself. The brand awareness of one product in the costumers’ mind is really important to notice and organize. Because of the importance of organizing brand awareness of one product, the objective of this research is to measure the brand awareness of the consumers’ of note book towards note book in Zyrex brand. The population in this research is the users of note book in Yogyakarta. The numbers of sample in this research are 100 people. The research uses convenience sampling that is the sampling method based on the easy and accessible selection of population members in getting information. Meanwhile, the sample in this research is those who use note book. The measurement of brand awareness is started by the questionnaire data tabulation; continued by the questionnaire data classification about top of mind, brand recall, brand recognition, and unaware of brand then continued by the percentage accounting. Based on the test done and the numbers of users, most of respondents use notebook of Acer brand. Whereas based on the level of awareness, for top of mind, many respondents remember the Acer brand firstly. Based on the brand recall, many respondents remember Compaq as the second brand of notebook they are able to remember. In addition, for the brand recognition, it shows that there are some respondents need to remind about the notebook brand of Zyrex